Effect of Mulching Techniques and Irrigation Levels on Onion (Allium cepa L.) Growth Parameters Under Drip Irrigation System During Dry Season of Western Ethiopia - Tasisa Temesgen Tolossa (Turkish Journal of Agriculture: Food Science and Technology)
The increasing scarcity and competition for irrigation water entails adoption of innovative practices that increase efficient water use. The objective of this research was to compare different mulching techniques and investigated the combined effect of irrigation levels under drip irrigation system based on the parametric evaluation system in western part of Ethiopia during the 2018 dry season. A factorial combination of five levels of water (namely 100%, 80% and 70%, 60% and 50%ETc) combined with three mulch treatments (namely, Normal Mulch (NM), Straw Mulch (SM) and Plastic Mulch (PM)) with three replications. The analysis of variance showed that, days to 50% maturity, leaf number per plant, mean leaf length, plant height and leaf area were significantly affected by the main effects of deficit irrigation levels and mulching materials. The interaction effects of deficit irrigation levels and mulching materials significantly influenced plant height, number of leaf per plant, plant height, Leaf length and Leaf area of the onion. The present study suggests that, in water scarce area, farmers are advised to adopt deficit irrigation level with 80% ETc under plastic mulch. It is important even to undertake similar studies at different seasons with different varieties in consideration of their cost benefit analysis. However, if water is not a limiting factor, farmers are advised to apply full irrigation water application under plastic mulch.